2020
DOI: 10.1177/2382120520913270
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Expert Mind: Integration Method for Revising the ACES Medical Simulation Curriculum

Abstract: Purpose: This article shares our experience developing an integrated curriculum for the ACES (Acute Critical Event Simulation) program. The purpose of the ACES program is to ensure that health care providers develop proficiency in the early management of critically ill patients. The program includes multiple different types of educational interventions (mostly simulation-based) and targets both specialty and family physicians practicing in tertiary and community hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Simulation education is fast becoming a key strategy to improve the knowledge and clinical performance of practitioners working in hospitals (Cardinal et al, 2020; Shah et al, 2019). Simulation activities link the theoretical learning from the classroom with practical, real‐life clinical scenarios (Cardinal et al, 2020; Piryani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation education is fast becoming a key strategy to improve the knowledge and clinical performance of practitioners working in hospitals (Cardinal et al, 2020; Shah et al, 2019). Simulation activities link the theoretical learning from the classroom with practical, real‐life clinical scenarios (Cardinal et al, 2020; Piryani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Simulation education is fast becoming a key strategy to improve the knowledge and clinical performance of practitioners working in hospitals (Cardinal et al, 2020; Shah et al, 2019). Simulation activities link the theoretical learning from the classroom with practical, real‐life clinical scenarios (Cardinal et al, 2020; Piryani et al, 2019). An earlier literature review revealed that a range of interactive education interventions and strategies for health care practitioners have been undertaken to improve delirium care across clinical settings (Coyle et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Simulation teaching has established an important position in medical education, but according to existing research and literature at home and abroad, simulation content is primarily available in the fields of anesthesia, first aid, and critical illness (2). However, there are few reports on simulation teaching courses with nursing Original Article Application of in situ simulation teaching in the training of trainee nurses to respond to emergencies emergency incidents as the main content, especially in situ simulation teaching (3). Traditional theoretical teaching can only educate students about the corresponding knowledge points, and cannot enable students to fully and proficiently master clinical thinking and processing procedures, and cannot meet the requirements of the new model of medical education.…”
Section: Introductionmentioning
confidence: 99%